Do atmospheric CO2 concentration increase, climate and forest management affect iWUE of common beech? Evidences from carbon isotope analyses in tree rings. (22nd March 2018) - Rezaie, Negar; D'Andrea, Ettore; Bräuning, Achim; Matteucci, Giorgio; Bombi, Pierluigi; Lauteri, Marco
Abstract: Beech is one of the most important forest tree species in Europe, hence possible adverse factors affecting its physiology and productivity can have strong ecological and economic impacts. In this context, four beech forests along a latitudinal gradient from southern Apennines to middle European lowlands were selected for chronological determinations of carbon isotope composition (δ 13 C) in tree-ring cellulose. The main objectives of this study were to assess (i) the effect of climate on the carbon signature of tree-ring cellulose (δ 13 C); (ii) the physiological response to recent CO2 concentration increment and to climatic variation; and (iii) the relationship between intrinsic water-use efficiency (iWUE, here the average long-term ratio of net photosynthesis to stomatal conductance) and growth of trees in different sites since 1950. Our results demonstrated that site climatic conditions peculiarly affect δ 13 C. In northern sites, a climatic control of summer precipitation and temperature on stomatal conductance was demonstrated by their opposite correlations with δ 13 C, negative and positive, respectively. Furthermore, an 'earliness effect' was suggested by a significant relationship between spring temperature and δ 13 C in the coldest sites and by a positive one between winter temperature and δ 13 C in the warmest ones. In all the study sites, during the maturity phase, a positive correlation between the increment of CO2 and iWUE was observed, due to an active response of trees to CO2 increment. This increment of CO2 was the main driver of the long term increasing trend of iWUE, resulting by an active response of trees to CO2 fertilization. Moreover, precipitation mostly influences positively and negatively the inter-annual variations of iWUE of the southernmost and northernmost sites, respectively. Overall, we observed a mean increment of 40% of iWUE. Moreover, the sensitivity of iWUE to the increase of CO2 was different between the northernmost and southernmost sites. Increasing iWUE was correlated to growth in the two sites during the release phase and we hypothesize a positive effect of silvicultural treatments.